Innovation of Hyperbaric Oxygen Therapy and Stichopus hermanii to The Amount of Macrophages in Periodontal Ligaments in Pressure and Tension Areas During Orthodontic Tooth Movement - Jessica Jenuary Yasin; Arya Brahmanta; Agni Febrina Pargaputri (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2019)
Background: The prevalence of malocclusion in Indonesia reaches 80%, causing orthodontic treatment needs to increase. Orthodontic treatment takes a long time around 15-24 months so additional therapy is needed to accellerate the orthodontic treatment process. Hyperbaric oxygen therapy (HBOT) and Stichopus hermanii (golden sea cucumber) which contain bioactive ingredients can work synergistically to reduce inflammatory cytokines. Purpose: To determine the effect of HBOT and Stichopus hermanii on the number of macrophages in periodontal ligament of pressure and tension area in the process of orthodontic tooth movement. Material and Methods: This research used Randomized Post Test Only Control Group Design. A sample of 30 marmot was randomly divided into 5 groups: negative groups (K-), positive groups (K+), Stichopus hermanii treatment group (P1), HBOT group (P2), and combination (P3). On K+ and treatment groups, maxillary incisors of marmot is installed helical spring in order to move the teeth to distal. Analysis of the number of macrophages histologically using Hematoxylin Eosin (HE) staining. And then tested using the Kruskal-Wallis test, and the Mann Whitney Wilcoxon test. Result: The research data showed a decrease of mean average number of macrophages in the pressure area, K (-): 1.90 ± 0.41; K (+): 4.40 ± 1.14; P1: 4,30 ± 0,90; P2: 3.60 ± 0.54; P3: 2.90 ± 0.41 and the mean number of machrophages in tension area also descreased, K (-): 2.00 ± 0.35; K (+): 4.00 ± 1.00; P1: 4,30 ± 0,27; P2: 4,10 ± 0,65; P3: 3.60 ± 0.65. Conclusion: The combination of HBOT and Stichopus hermanii decreases the number of macrophages in the pressure and tension area in orthodontic tooth movement.